Pengembangan E-Module Berbasis Liveworksheet pada Materi Energi dan Usaha untuk Siswa SMK Kelas XI - Yeni Nora Wiwi; Rizky Ema Wulansari; Dedy Irfan; Muhammad Giatman (Jurnal Penelitian Pendidikan IPA, 2025)
This research aims to develop, assess the validity, and determine student responses to a Liveworksheet-based e-module on Energy Efficiency in Small and Medium Enterprises as a learning resource for vocational students. The research and development (R&D) method employed the ADDIE model, which includes stages of Analysis, Design, Development, Implementation, and Evaluation. The e-module was developed using the Liveworksheet application to enhance interactivity and engagement. Data analysis of validity and student responses was conducted quantitatively using descriptive percentage techniques. The results show that the e-module achieved an average validity score of 92.62% from material experts, media experts, and education practitioners, categorized as very good and suitable for implementation. Student response tests conducted in two stages—small class trials with a score of 92.5% and large class trials with a score of 91.34%—both fall within the very good category. These results indicate that the developed e-module is valid, practical, and feasible to be used as an effective digital learning resource in vocational education.